HVAC System - Sheikholeslami Kandelousi, Mohsen (IntechOpen, 2018)
In this book, various aspects of heating, ventilation, and air-conditioning (HVAC) systems are investigated. HVAC systems are milestones of building mechanical systems that provide thermal comfort for occupants accompanied with indoor air quality. HVAC systems can be classified into central and local systems according to multiple zones, location, and distribution. Primary HVAC equipment includes heating equipment, ventilation equipment, and cooling or air-conditioning equipment. Central HVAC systems are located away from buildings in a central equipment room and deliver the conditioned air by a delivery ductwork system. Central HVAC systems contain all-air, air-water, or all-water systems. Two systems should be considered as central such as heating and cooling panels and water-source heat pumps.